Dialectical Behavior Therapy in Managing Emotional Dysregulation and Self-Injurious Behaviors: Assessment, Intervention, and Clinical Applicability - Sabri, Farhana; Saputra, Andika Ari (Buletin Konseling Inovatif, 2026)
Dialectical Behavior Therapy (DBT) is an empirically supported intervention initially designed for individuals diagnosed with Borderline Personality Disorder (BPD) who present with self-injurious behaviors. The present article aims to evaluate the utility of DBT in addressing emotional dysregulation and maladaptive behavioral patterns across a range of clinical populations. The analysis encompasses assessment and case conceptualization, intervention strategies, evaluation of therapeutic outcomes, and termination protocols. Consideration is also given to the implementation of DBT in group settings and the influence of cultural factors on its effectiveness. Evidence from previous studies demonstrates that DBT contributes to significant reductions in self-harm, emotional distress, and psychiatric symptomatology in various diagnostic groups. Nevertheless, challenges related to cultural adaptation and the complexity of treatment delivery persist. It is concluded that DBT provides a systematic and comprehensive approach for the management of emotional dysregulation, although further modifications are warranted to improve its cultural relevance and accessibility.